1998
DOI: 10.1046/j.1469-8137.1998.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Branched absorbing structures (BAS): a feature of the extraradical mycelium of symbiotic arbuscular mycorrhizal fungi

Abstract: The present work describes the morphogenesis and cytological characteristics of ' branched absorbing structures ' (BAS, formely named arbuscule-like structures, ALS), small groups of dichotomous hyphae formed by the extraradical mycelium of arbuscular mycorrhizal (AM) fungi. Monoxenic cultures of the AM fungus Glomus intraradices Smith & Schenck and tomato (Lycopersicum esculentum Mill.) roots allowed the continuous, nondestructive study of BAS development. These structures were not observed in axenic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(94 citation statements)
references
References 43 publications
5
82
1
3
Order By: Relevance
“…Fungos micorrízicos arbusculares (FMA) podem constituir outra alternativa para incrementar a produção de mudas, reduzindo a necessidade de aplicação desses insumos, sobretudo considerando a dependência do maracujazeiro à micorrização . Expandindo a zona de absorção da raiz, pelo desenvolvimento de hifas que se ramificam, explorando e absorvendo maior quantidade de nutrientes minerais do solo, os FMAs podem acarretar maior crescimento das plantas, em menos tempo (Bago et al, 1998). Além da melhoria na nutrição, a inoculação com FMA tem sido responsável pelo melhor estabelecimento de mudas no transplantio para o campo, conferindo também maior tolerância a patógenos do solo (Smith & Read, 1997).…”
Section: Introductionunclassified
“…Fungos micorrízicos arbusculares (FMA) podem constituir outra alternativa para incrementar a produção de mudas, reduzindo a necessidade de aplicação desses insumos, sobretudo considerando a dependência do maracujazeiro à micorrização . Expandindo a zona de absorção da raiz, pelo desenvolvimento de hifas que se ramificam, explorando e absorvendo maior quantidade de nutrientes minerais do solo, os FMAs podem acarretar maior crescimento das plantas, em menos tempo (Bago et al, 1998). Além da melhoria na nutrição, a inoculação com FMA tem sido responsável pelo melhor estabelecimento de mudas no transplantio para o campo, conferindo também maior tolerância a patógenos do solo (Smith & Read, 1997).…”
Section: Introductionunclassified
“…One explanation may be that as the crop matures a reduction in C supply to AM fungi between R5 and R6 stage of corn may trigger the production of glycolipids in spore-related structures formed by symbiotic fungi. Bago et al (1998) observed in Glomus intraradices that arbuscules develop along intraradical, intercellular hyphae or intracellular coils, while branched absorbing structures (BAS) are formed on extraradical mycelia, possibly associated with spore formation. Arbuscules and BAS share several cytological characteristics: both contain numerous nuclei, mitochondria, glycogen deposits, lipid globules, abundant polyvesicular bodies and electrodense granules inside small vacuoles (Bonfante-Fasolo, 1984;Bago et al, 1998).…”
Section: Article In Pressmentioning
confidence: 99%
“…Bago et al (1998) observed in Glomus intraradices that arbuscules develop along intraradical, intercellular hyphae or intracellular coils, while branched absorbing structures (BAS) are formed on extraradical mycelia, possibly associated with spore formation. Arbuscules and BAS share several cytological characteristics: both contain numerous nuclei, mitochondria, glycogen deposits, lipid globules, abundant polyvesicular bodies and electrodense granules inside small vacuoles (Bonfante-Fasolo, 1984;Bago et al, 1998). In plants, steryl glucosides and their acylated derivatives (GLFA) are located in microsomal and mitochondria membranes (Harwood, 1977).…”
Section: Article In Pressmentioning
confidence: 99%
“…Development of extraradical mycelium under aseptic conditions is often accompanied by the production of so-called arbuscule-like structures (ALS) (Bago et al, 1998a) or branched absorbing structures (BAS) (Bago et al, 1998b). The authors suggest the possible implication of the ALS/BAS in the exchange sites between AM fungi and host plants.…”
Section: Fundamental and Practical Studiesmentioning
confidence: 99%